2021
DOI: 10.1159/000515790
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of BRCA1/2 Mutation-Positive Breast Cancer

Abstract: <b><i>Purpose:</i></b> The <i>BRCA1/2</i> gene is the most well-known and studied gene associated with hereditary breast cancer. <i>BRCA1/2</i> genetic testing is widely performed in high-risk patients of hereditary breast cancer in Korea. This study aimed to investigate the clinicopathological characteristics of <i>BRCA1/2</i> mutation-positive breast cancer patients. <b><i>Methods:</i></b> The clinical data of 188 Korean brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
3
6
1
Order By: Relevance
“…Clinical factors such as onset age and the family history of breast or ovarian cancer were significantly associated with mutations in BRCA1/2 in our study, which was consistent with an Asian study [30]. Luminal B and TNBC subtypes were considered high-risk factors of BRCA1/2 P/LP mutation [37]. Likewise, we identified that luminal B or TNBC subtype patients did have a higher frequency of BRCA1/2 P/LP mutation.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical factors such as onset age and the family history of breast or ovarian cancer were significantly associated with mutations in BRCA1/2 in our study, which was consistent with an Asian study [30]. Luminal B and TNBC subtypes were considered high-risk factors of BRCA1/2 P/LP mutation [37]. Likewise, we identified that luminal B or TNBC subtype patients did have a higher frequency of BRCA1/2 P/LP mutation.…”
Section: Discussionsupporting
confidence: 90%
“… 33 BRCA1 and BRCA2 are the tumor suppressor genes, and highly penetrating mutations in these genes result in a loss of tumor suppressor function and thus an increased risk of ovarian cancer. 34 Understanding whether the unique clinical and pathological features of ovarian cancer are associated with the BRCA1/2 gene mutation is essential to mitigate prognosis differences in the female population.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on dual primary BC were mainly focused on the summary of clinicopathological practices and genome detection [5][8]. Referring to other machine learning-based BC prediction cases [33] [35], this study applied machine learning to the dual primary prediction of BC for the first time. Our method can aid doctors in the diagnosis and treatment of first-episode BC with theoretical and medical significance.…”
Section: P R E P R I N Tmentioning
confidence: 99%